Pengembangan Media Game Edukasi “Tebak Pakaian Adat” Untuk Materi Keragaman Budaya Siswa Kelas IV Sekolah Dasar - Bisi, Maria Oktaviana Soares Bui; Mukmin, Bagus Amirul; Aka, Kukuh Andri (Universitas Muhammadiyah Magelang, 2026)
This study aimed to develop an educational game entitled Guess the Traditional Clothing as a learning medium for the topic of cultural diversity for fourth-grade students at SDN Bandar Lor 3 and to determine its validity, practicality, and effectiveness. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research participants included material experts, media experts, a fourth-grade teacher, and fourth-grade students at SDN Bandar Lor 3. Data were collected through observations, interviews, questionnaires, documentation, and learning achievement tests. The data were analyzed using descriptive qualitative and quantitative techniques. The results indicated that the developed media achieved a validity score of 91.6%, categorized as highly valid. The practicality was demonstrated by positive responses from the teacher (98%) and students (98.5%), indicating that the media was highly practical. Furthermore, the effectiveness of the media was confirmed by an 88% learning mastery rate in the large-scale implementation. Therefore, the Guess the Traditional Clothing educational game is considered highly valid, practical, and effective for supporting the learning of cultural diversity in elementary schools.